Letter : Aid for Spanish seamen - Marchbank, John
025a-0127-001 TELEGRAMS BEWARE NORWEST LONDON TELEPHONE EUSTON 4771 (five lines) The National Union of Railwaymen J. MARCHBANK GENERAL SECRETARY G.W. BROWN ASSISTANT GENERAL SECRETARY Unity House Euston Road LONDON N.W.1. Your ref IN YOUR REPLY REFER TO F.M.A. 2. 17th March, 1939. H. V. Tewson, Esq., Assistant Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Sir, AID FOR SPANISH SEAMEN. With reference to the meeting of the British Section of the International Transport Workers' Federation held at Transport House on the 13th instant; I have to say that my Executive Committee gave consideration to the appeal made on behalf of Spanish Seamen stranded in this country, and decided to make a grant of £500. A cheque for this amount will be drawn and forwarded to you next week. Yours faithfully, J. Marchbank 292/946/25a/127